Estudo da variabilidade da região codificadora e 3'não traduzida do gene HLA-F no Brasil - Lima, Thalitta Hetamaro Ayala [UNESP] (2015)
HLA-F is a non-classical HLA class I gene and is distinguished from its classical counterparts by low allelic polymorphism and distinctive expression patterns. The exact function of HLA-F remains unknown. It is believed that HLA-F has tolerogenic and immune modulatory features. Currently, there is little information regarding the HLA-F allelic variation among humans and the available studies have evaluated only a fraction of the HLA-F gene segment and/or have searched for known alleles only. Here we present a strategy to evaluate the complete HLA-F variability including its regulatory segments (promoter and 3'UTR) by using massive parallel sequencing (or second generation sequencing) procedures. HLA-F variability was surveyed on 196 individuals from the Southeast of Brazil. The results indicate that the HLA-F gene is indeed conserved at the protein level, in which the three coding haplotypes detected encode for only four different HLA-F molecules, and one of these molecules represent 82.45% of all. However, HLA-F worldwide haplotype variability is much higher than our current knowledge. The 3'UTR presented few variable sites and well-defined haplotypes that are usually associates with the same coding alleles. This protein conservation is probably a consequence of the HLA-F's key role in the immune system physiology